2020
DOI: 10.1108/jhlscm-08-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Organization theory in humanitarian operations: a review and suggested research agenda

Abstract: PurposeThe purpose of this paper is to review the current application of organization theory (OT) in the humanitarian supply chain (HSC) and identify the future OT-based research opportunities that can advance knowledge of humanitarian operations.Design/methodology/approachThe study uses a systematic literature review methodology to identify the current status and future direction of the OT-based study in HSC literature. The applied theories are those that have been mentioned in at least two research articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 118 publications
0
36
0
Order By: Relevance
“…In this sense, dynamic capabilities (DCs) view has recently gained attention of HSCM-focused investigations thanks to its facilitating function of creating new static capabilities or modifying the existing ones all along the SC partners (Defee and Fugate, 2010). As an extension of resource-based view, DCs view is believed to provide better solutions to the volatile environment of HSCs due to its strength to combine, transform and reconfigure the existing competencies and resources to match the requirements of a changing environment (Altay et al, 2018;Prakash et al, 2020;Tabaklar, 2017;Teece et al, 1997, p. 515). For example, the positive and significant effect of supply chain agility (SCA) and supply chain resilience (SCR) DCs to the Indian humanitarian supply chain management (HSCM) in the disaster preparation and response phases is an evidence of the importance of using DCs view in HSCM (Altay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, dynamic capabilities (DCs) view has recently gained attention of HSCM-focused investigations thanks to its facilitating function of creating new static capabilities or modifying the existing ones all along the SC partners (Defee and Fugate, 2010). As an extension of resource-based view, DCs view is believed to provide better solutions to the volatile environment of HSCs due to its strength to combine, transform and reconfigure the existing competencies and resources to match the requirements of a changing environment (Altay et al, 2018;Prakash et al, 2020;Tabaklar, 2017;Teece et al, 1997, p. 515). For example, the positive and significant effect of supply chain agility (SCA) and supply chain resilience (SCR) DCs to the Indian humanitarian supply chain management (HSCM) in the disaster preparation and response phases is an evidence of the importance of using DCs view in HSCM (Altay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of DCs approach to generate dynamic solutions to HSCM problems by the HSCM literature is evident, the existing HSCM literature reviews (LRs) have not systematically investigated the HSCM studies that specifically applied DCs approach. The existing HSCM-oriented LRs have touched briefly on the importance of DCs in humanitarian context (Agarwal et al, 2019;Behl and Dutta, 2019;Prakash et al, 2020;Soosay and Hyland, 2015;Stechemesser et al, 2015;Tabaklar et al, 2015), yet they have not discussed the role of DCs systematically and in detail. In addition, when the author searched the literature with the combination of "dynamic capability/capabilities" and "literature review" keywords, it was observed that the dominant number of studies are organizational management focused and only 1 out of 45 papers investigated crisis response at organizational level (Adrot and Robey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Maroun & Van Zijl 2016;Masocha & Fatoki 2018). Mimetic processes have also been suggested to influence both disaster response-oriented organisations and their increasing focus on DRR in recent decades (Prakash et al 2020). This is linked to Dimaggio and Powell's (1983) last type of processes behind institutional isomorphism; normative processes associated with professionalisation and professional culture.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also argue for combining, contrasting and extending these theories to gain multiple, complementary and advanced perspectives that shed light on HLSC sourcing relationships, competitiveness, echelons of production and distribution, etc. Following a similar line of reasoning, Prakash et al (2020) use criticisms of limited theoretical grounding in current HLSC research to argue primarily for organisation theory as a lens to shed light on orchestration for the unique contexts posed by cases of humanitarian emergencies and disasters. The authors review applied theories in HLSC settings (resource-based, resource dependence, social exchange and contingency theory) and propose additional theories (institutional, stakeholder, transactional cost and information theories) for future studies based on conceptual similarities with supply chains and applicability for explaining information asymmetry within HLSCs.…”
Section: Research Background 21 Crisis and Humanitarian Logistics And Supply Chainsmentioning
confidence: 99%